Penerapan Metode Kooperatif pada Kompetensi Afektif dan Kongnitif Siswa Kelas IV MI Muhammadiyah 1 Sukodadi - Rizka Rismawanda; Linaria Arofatul Ilmi Uswatun Khasanah (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2021)
One way to increase student saturation in the learning process is through cooperative methods in Civics subjects, the purpose of this research is to improve Civics learning about globalization in the realm of affective and cognitive competencies. This research is Classroom Action Research with a qualitative approach consisting of two cycles. Each cycle consists of four stages, namely planning, implementing actions, observing or observing and reflecting. This research was conducted at MI Muhammadiyah I Sukodadi Lamongan in fourth grade students consisting of 13 male students and 12 female students using research methods in the form of tests, observations, interviews and questionnaires. The results showed that children's affective and cognitive abilities increased from cycle I to cycle II. This can be described as follows: Increasing the effectiveness of student learning outcomes in the use of cooperative methods in Civics learning increased from 70.66 to 79.00. Improved performance of students' attitudes and learning interest in the use of cooperative methods in Civics learning increased from 68.66 to 76.50. So it can be concluded that cooperative methods can improve students' affective and cognitive competencies.